Shamanism in Siberia Sound and Turbulence in Cursing Practices in Tuva - Stelmaszyk, Mally (Taylor & Francis, 2022)
The focus of this book is on the phenomenon of cursing in shamanic practice and everyday life in Tuva, a former Soviet republic in Siberia. Based on extensive anthropological fieldwork where the author interacted with a wide range of people involved in cursing practices, the book examines Tuvans’ lived experience of cursing and shamanism, thereby providing deep insights into Tuvans’ intimate and social worlds. It highlights especially the centrality of sound: how interactions between humans and non-humans are brought about through an array of sonic phenomena, such as musical sounds, sounds within words and non-linguistic vocalisations, and how such sonic phenomena are a key part of dramatic cursing events and wider shamanic performance and ritual, involving humans and spirits alike. Overall, the book reveals a great deal about occult practices and about social change in post-Soviet Tuva.